Audit of Enterprises Revenue Cycle - Pečiūra, Vilmantas; Staškevičius, Juozapas Audvydas (Ekonomika, 1998)
One effective way to perform an audit is to classify transactions into “cycles” of related activities. A revenue cycle is common for sales and manufacturing enterprises.Auditors should test financial statements assertions - existence, completeness, rights and obligations, valuation, and presentation and disclosure - embodied in the revenue cycle.Auditors should evaluate the control risk of revenue cycle. If the control risk is low, the number of substantive audit procedures can be reduced.Confirmations is a standard audit procedure for accounts receivable. Positive confirmations provide more reliable evidence.Auditors should evaluate the adequacy of the allowance for doubtful accounts.